2017
DOI: 10.3389/fnhum.2017.00241
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Response Alterations in Sensorimotor Areas as a Function of Barbell Load Levels during Squatting: An fNIRS Study

Abstract: Functional near-infrared spectroscopy (fNIRS) serves as a promising tool to examine hemodynamic response alterations in a sports-scientific context. The present study aimed to investigate how brain activity within the human motor system changes its processing in dependency of different barbell load conditions while executing a barbell squat (BS). Additionally, we used different fNIRS probe configurations to identify and subsequently eliminate potential exercise induced systemic confounders such as increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 86 publications
(110 reference statements)
2
30
1
1
Order By: Relevance
“…This finding is further strengthened by previous studies demonstrating that higher cadences (MacIntosh et al 2000) and intensities (Macdonald et al 2008) during a cycling task are associated with a higher leg muscle activation. Hence, it is reasonable to assume that an increased recruitment of muscle fibers requires higher levels of neural resources in motor-related brain areas not only on a regional but also on a network level (Kenville et al 2017). The fact that we observed intensity-dependent changes during cycling in a single brain region only (left PMC) does certainly not indicate that this area is exclusively responsible for modulating brain areas during increased workload during cycling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is further strengthened by previous studies demonstrating that higher cadences (MacIntosh et al 2000) and intensities (Macdonald et al 2008) during a cycling task are associated with a higher leg muscle activation. Hence, it is reasonable to assume that an increased recruitment of muscle fibers requires higher levels of neural resources in motor-related brain areas not only on a regional but also on a network level (Kenville et al 2017). The fact that we observed intensity-dependent changes during cycling in a single brain region only (left PMC) does certainly not indicate that this area is exclusively responsible for modulating brain areas during increased workload during cycling.…”
Section: Discussionmentioning
confidence: 99%
“…This neuroimaging method has been established as a valuable tool for measuring neurovascular coupling (Liao et al 2013; Pinti et al 2018) during physical activity and exercise involving the quantification of chromophore concentrations resolved from the measurement of relative changes in oxygenated (Hb) and deoxygenated hemoglobin (HHb) (Obrig et al 1996; Obrig and Villringer 2003; Perrey 2008; Strangman et al 2002). Previous studies have demonstrated that fNIRS is an appropriate and reliable method for measuring neurovascular coupling in adults during both simple motor tasks (see Leff et al 2011) as well as complex body movements such as walking/running (Harada et al 2009; Holtzer et al 2011; Suzuki et al 2004), rowing (Nielsen et al 1999), squatting (Kenville et al 2017), juggling (Carius et al 2016) or playing table tennis (Balardin et al 2017). Moreover, cycling on an ergometer has been established in several studies as a standardized and comparable task for measuring brain activation during exercise using fNIRS (Ohyanagi et al 2018; Radel et al 2018; Tempest and Parfitt 2016; Tempest and Reiss 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent fNIRS studies in non-athletes have found that hemodynamic responses in bilateral superior parietal lobes vary as a function of physical load during low- to moderate-intensity barbell squat (Kenville et al, 2017). Another study demonstrated that the shape and amplitude of the deoxyhemoglobin response curve for the motor cortex was not significantly different between indoor and outdoor cycling (albeit on a straight and level bike lane; Piper et al, 2014).…”
Section: Portable Neurophysiological Systems For Sports Researchmentioning
confidence: 99%
“…Based on the drawbacks of EEG and the advantages of fNIRS, fNIRS is currently better suited for measurements of changes in cortical brain activity during physical exercises in unconstrained environments [50,102,103]. In fact, fNIRS has been applied during a variety of physical exercises such as juggling [104], balancing [105][106][107][108][109][110], walking (for review see [111,112]), resistance exercises [113][114][115][116], dancing [117][118][119], tai chi [120,121], climbing [122], synchronized swimming routines [123], table tennis [124], running [125][126][127], and predominantly during cycling . Furthermore, fNIRS was used to monitor cerebral oxygenation during stationary cycling even in special cohorts, such as cardiac patients [166][167][168][169].…”
Section: Which Portable Neuroimaging Tools Can Be Used To Assess Braimentioning
confidence: 99%